The Metaphorical Use of “Call” by Paul: Romans as a Test Case - SAVKOVIĆ, Fiva (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
Ongoing dissertation at the Faculty of Orthodox Theology of the University of Belgrade, Serbia. Project Abstract: Modern studies of the Pauline epistles have long noted the importance of metaphor as an element of Paul’s thought and expression. In the words of Richard B. Hays, “Paul, the missionary preacher, is at least as much poet as he is theologian […] throughout his writings, Paul’s language sparkles with the veiled energy of metaphor and allusion.”[1] James Dunn notes that among the various metaphors employed in Paul’s discourse, the term καλεῖν is one of the apostle’s more significant soteriological metaphors which originate from everyday life of his lifetime, but he does not explore this important idea further.[2] By contrast, Kristal Stendahl and others[3] have stressed the importance of Paul’s concept of “divine calling,” but have lacked a comprehensive investigation into its metaphorical nature. In order to contribute significantly to the field of New Testament exegesis, my dissertation attempts to fill this gap in scholarship by focusing on the metaphorical aspects of Paul’s divine call language. [1] R. B. Hays, “Introduction to the Second Edition”, in: The Faith of Jesus Christ: The Narrative Substructure of Galatians 3:1–4:11, 2nd ed., Eerdmans Publishing, Grand Rapids 2002, xxi–l, p. xxxiii. Italic is authorial. [2] Cf. J. D. G. Dunn, The Theology of Paul the Apostle, Eerdmans Publishing, Grand Rapids 1998, 329. [3] Cf., for example, K. Stendahl, “Call Rather Than Conversion”, in: Paul among Jews and Gentiles, and Other Essays, Fortress Press, Philadelphia 1976, 7–23; B. R. Gaventa, From Darkness to Light, Fortress Press, Philadelphia 1986; A. F. Segal, Paul the Convert: the Apostolate and Apostasy of Saul the Pharisee, Yale University Press, Yale 1990; E. Kobel, „Paulus in seiner Welt“, in: Paulus als interkultureller Vermittler: Eine Studie zur kulturellen Positionierung des Apostels der Völker, Verlag Ferdinand Schöningh, Paderborn 2019, 65–132. C. Strecker, Die liminale Theologie des Paulus: Zugänge zur paulinischen Theologie aus kulturanthropologischer Perspektive, Vandenhoeck & Ruprecht, Göttingen 1999. Although I. Hussey stresses importance of call metaphoricity in his study of Paul’s soteriological use of call, he doesn’t go deep into it. Cf. I. Hussey, The Soteriological Use of Call by Paul and Luke, ACT Monograph Series, Oregon 2018.